PEMBANGUNAN MASYARAKAT ALTERNATIF MODEL DEMOCRATIC PARTICIPATORY - Zainal Fadri (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2020)
Development is a definite step undertaken by a country in achieving a good standard of living. Economic development and social development become a reflection of the success of the sovereign state so that it becomes a high bargaining value in international relations. Development in Brazil and Indonesia are both affected by the crisis that occurred in the world, thus presenting foreign entrapments and interventions that will affect every policy taken. To rise from the economic downturn, the state must be present in determining the right development model to overcome the problems that occur as a result of failure. The method used in this paper is the method of library research with a comparative analysis approach. Study material is taken from books and journals that are relevant to the theme of the writing. The results of this paper describe an alternative model of democratic participatory development into an effort to increase development, both in the social and economic fields. Community participation in development in Porto Alegre Brazil shows a significant change towards improving welfare, while at the same time being a lesson for Indonesia in making development policies optimally.